2021
DOI: 10.3390/ijms221910657
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Induces Meningeal Niche Remodeling through TrkB-Mediated Signaling

Abstract: Neural precursors (NPs) present in the hippocampus can be modulated by several neurogenic stimuli, including environmental enrichment (EE) acting through BDNF-TrkB signaling. We have recently identified NPs in meninges; however, the meningeal niche response to pro-neurogenic stimuli has never been investigated. To this aim, we analyzed the effects of EE exposure on NP distribution in mouse brain meninges. Following neurogenic stimuli, although we did not detect modification of the meningeal cell number and pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…However, since the complexity of our behavioural paradigms and the three factors involved (EE, fluoxetine, living conditions), we cannot exclude that the behavioural outcomes observed might be the result of a complex interplay between other molecular mechanisms (Begni et al 2020 ; Eckert and Abraham 2013 ; Solinas et al 2021 ; van Praag et al 2000 ; Zorzin et al 2021 ). For instance, the different ‘EE experience’ due to the specific EE complexity and features used in social and isolated mice (2-level cage with littermates vs. new standard home cage without social component) may also represent another factor that could affect the efficacy of EE-fluoxetine combination in inhibiting sucrose-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the complexity of our behavioural paradigms and the three factors involved (EE, fluoxetine, living conditions), we cannot exclude that the behavioural outcomes observed might be the result of a complex interplay between other molecular mechanisms (Begni et al 2020 ; Eckert and Abraham 2013 ; Solinas et al 2021 ; van Praag et al 2000 ; Zorzin et al 2021 ). For instance, the different ‘EE experience’ due to the specific EE complexity and features used in social and isolated mice (2-level cage with littermates vs. new standard home cage without social component) may also represent another factor that could affect the efficacy of EE-fluoxetine combination in inhibiting sucrose-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the research on the mechanism of EE affecting neurogenesis is still being explored. Early experiments have shown that EE can enhance the growth factors that promote neurogenesis, including brain-derived neurotrophic factor (BDNF; Zorzin et al, 2021 ), nerve growth factor (NGF; Pham et al, 1999 ), glial cell-derived neurotrophic factor (GDNF; Young et al, 1999 ), vascular endothelial cell growth factor (VEGF; Cao et al, 2004 ). A recent study suggests that EE and exercise can also enhance adult hippocampal neurogenesis through fibroblast growth factor receptor (FGFR), which induces the proliferation of stem and progenitor cells (Grońska-Pęski et al, 2021 ).…”
Section: The Effects Of Ee On Neurodevelopment In Brainmentioning
confidence: 99%
“…In experimental models, EE exerts a positive role in promoting regeneration, neurogenesis, and CNS remodeling. Exposure prevents relapse, enhances attention performance, reduces anxiety levels during development, prevents DNA methylation changes brought by aging, and enhances neurogenesis by increasing NPCs ( Korkhin et al, 2020 ; Zocher et al, 2021 ; Zorzin et al, 2021 ; Pintori et al, 2022 ). Similarly, exercise promotes positive effects on neurogenesis, trophic factor secretion, motor recovery following ischemia, cognitive and motor function, and neuroprotection ( Pang et al, 2006 ; Mang et al, 2013 ; Tsai et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%